A scandal at midnight - Burrows, Annie (Harlequin historicals., 2021)
From reluctant debutante to scandalous bride! After a disastrous first Season, Lady Daisy Patterdale is relieved to be back home with her books. Looking for peace, she rows out to the island on the lake, where she encounters Captain Benjamin Flinders, the Earl of Bramhall--who's been tricked and left there with no clothes! It's a scandalous encounter that rushes them straight to the altar... But despite her unwillingness to wed, Daisy's drawn to charismatic Ben. If only he felt more for her than a sense of duty...